(Information letter) Method of determining the frequency of pertussis infections by their serological prevalence - Volianskyi, Andrii; Smilyanska, Maia; Didorenko, Tetiana; Bolshakova , Halyna; Holubka , Olha (Annals of Mechnikov's Institute, 2024)
The interpretation of serological values ​​of PT-IgG MO/ml is proposed: 5 MO/ml – limit titer; 50–99 MO/ml - infection lasting for the remaining 3-5 years; ≥100 MO/ml – infection for the rest of the year. The use of this method makes it possible to increase the established frequency of pertussis infections beyond their serological spread, which means that populations will require additional pacification, preventive treatment and dynamic care, in turn; I will be able to develop more effective strategies for their control. Keywords: pertussis infections, serological prevalence.